Ð¡Ñ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð½Ð¾-Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ Ð¼ÐµÑ…Ð°Ð½Ð¸Ð·Ð¼Ñ‹ Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ ÑÐºÑÑ‚Ñ€ÐµÐ¼Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ Ð½Ð° Ñ‚ÐµÑ€Ð¼Ð¾Ñ€ÐµÐ³ÑƒÐ»ÑÑ‚Ð¾Ñ€Ð½Ñ‹Ðµ Ñ†ÐµÐ½Ñ‚Ñ€Ñ‹ Ð³Ð¸Ð¿Ð¾Ñ‚Ð°Ð»Ð°Ð¼ÑƒÑÐ° - Babijchuk, V. G.; Marchenko, V. S.; Babijchuk, G. A.; Marchenko, L. N.; Bondar, T. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The authors studied the central structural and functional effect mechanisms of periodic short term organism cooling in cryochamber (-120Â°C). There has been demonstrated a periodic increase of blood brain barrier (BBB) permeability stipulated by a long-term activation of the neuronsâ€™ synaptic apparatus of pre-optic hypothalamus area. There were presented the suppositions on the relation of cryotherapy therapeutic effect with the increase of functional activity in neurotransmitter-cyclic mononucleosides-retrograde messengers (NO, CO) system which effect was unified at the level of cytolemma and receptor-cytoskeleton complex.